The Grammar of Visual Design as a tool to read images: a reading experience with pre-service teachers - Soares Barbosa, Vania; Araújo, Antonia Dilamar (Calidoscópio, 2022)
Advances in digital technologies have made us immerse in an increasing world of images, turning us not only consumers, but also producers of multimodal texts. Consequently, communication has become more and more visual, and conceptions on what is to be literate in the 21st Century need to be rethought to prepare its citizens to read, interpret and express themselves through those texts. How to achieve it and what are the gains and losses from this achievement is a concern educators have, especially those in teaching training. This paper is part of a study that aimed at investigating the viability of teaching categories from the Grammar of Visual Design (Kress and van Leeuwen, 2006), as a tool to promote visual literacy when reading and viewing skills are integrated (Barbosa, 2017). In this part of the study, we discuss the meaning eight pre-services teachers made when reading an advertisement, and its implication to their visual literacy according to Callow’s model (2005). The results showed the rise of a reader-viewer (Serafini, 2014; Barbosa, 2017), who makes meaning on the verbal and the visual, more conscious, and aware of the importance of integrating those modes, but also more critical and structuralist, and less affective. Keywords: the grammar of visual design; visual literacy; teacher education.